Entre o real e o virtual: a educação a distância (EaD) como espaço para o educar (aprender e ensinar) pela pesquisa - Vieira, Leociléa Aparecida (2011)
The study we introduce here is inside the research line called: New Technologies in Education, what is part of the Education Doctorate Program from the Curriculum of the Pontifical Catholic University of São Paulo. The research had the following Objectives: a) Identify the facilities and difficulties found out by the teachers-students from the courses of post graduation named: Technologies and Distance Education and DE and the New Technologies ; through the research in the apprenticeship virtual ambience; b) To analyze the leading principles of pedagogic practical linked to the process of the knowledge construction and the way that the drill named: Scientific Research Methodology, contribute to the formation of the searching student meanwhile he or she is the producer of the knowledge. The starting conceptual point was framed by making the interlacement between technology and curriculum, while the literature revision concentrated about the knowledge history, the research as an educative principle and as a scientific principle. The investigation that is characterized by the case study enabled to form the two analyze categories: teaching and learning by searching and autonomy in the conception of Paulo Freire. To explain the collection instruments it was used the analyze of the contents inside the deposition of the twenty-one teachers-students and the eight teachers of the discipline Methodology of Scientific Research and Orientation of the Works to the Course Ending, the purpose of understanding the confrontation and the virtual and real challenges of the research subjects. During the development of the research it was observed that some barriers must be overcome by the students so as by the teachers, among them it is detached: a) Plagiarism; b) Reading lack; c) Understanding of that searching is much more than use Copy and Paste Keys; d) The culture absence that the student learn something, mo matter if it is in the virtual or in the real way; e) Resistance to the new; f) Dialoguing when writing the didactic materials; g) The virtual distance by itself what doesn‟t allow the eye by eye between who learns and who teaches. By ending the present study it was tried to show that educate or learn by searching, specially in DE, it should give to the student, the object of apprenticeship, the development of his or her autonomy supported by an educative proposal that allows the critical reading of the world, in the view of making a social and political construction that leads students and teachers to freedom